Moderating of SERVQUAL on E-WOM, Product Quality, and Brand Image on and E-commerce Purchase Intention - Pradana, Andi Fadel Pradana; Hasan, Sabri; Putra, Aditya Halim Perdana Kusuma; Kalla, Rastina (Golden Ratio of Mapping Idea and Literature Format, 2022)
This article presents the results of mapping taken from various sources as many as 20 articles on e-WOM, Product Quality and Brand Image as well as consumer behavior and purchasing power towards purchase intention. In the concept of marketing; word of mouth (WOM) is a noble goal of various business activities where the concept of WOM is as a form of advertising through voluntary recommendation activities from consumers to their social environment and groups. In digital activity, the concept of WOM then changed to e-WOM (electronic word of mouth). The presence of a product, word of mouth and also customer preferences are inseparable from the linkage of brand image attached to product elements and service quality. In general, Brand image is the current view of customers about a brand. Brand image can be defined as a collection of unique associations in the minds of target customers.